Determination of stabilizer concentration and process effect on the stability of milk-based cocoa beverage - Ozturk, Saniye Akyil; Icyer, Necattin Cihat; Karaca, Ali Can; Bekiroglu, Hatice; Sagdic, Osman; Toker, Omer Said (WILEY, 2025)
In the production of milk-based cocoa beverages, stability challenges such as sedimentation and creaming may arise due to the delicate balance of cocoa particles, proteins, and fat content, impacting the uniformity and texture of the final product. One of the most important hydrocolloids used to overcome these stabilization problems in milk-based products is kappa-carrageenan. In this study, the optimization process was carried out using central composite design by adding different proportions of kappa-carrageenan (0.01%-0.04%) and applying homogenization processes at different pressures (5-34 MPa) considering the norms of dairy industry. The effects of these independent variables on water-holding capacity (WHC), separation, creaming, pH, and viscosity values were investigated. Optimum sample (0.037% carrageenan and 19.38 MPa) had high WHC (97.26%), low viscosity (62.01 mPa s), and suitable separation and creaming values, indicating superior stability compared to market alternatives. The L*, a*, b* color values, particle size (Z-Ave), zeta-potential value, FTIR spectra, and microscope images were measured in the optimum samples and samples obtained from market. Image processing also highlighted that optimum sample had better stability than market samples considering entropy, variance, and homogeneity values. Additionally, this research presents an innovative approach by detailing the interactions between kappa-carrageenan and milk proteins, which are key to achieving the desired product stability. The fact that the levels of independent variables used in the study are appropriate for the industry will shed light on the studies to be carried out to produce products with the desired quality in the market.
Keywords: carrageenan; homogenization; image processing; microstructure; milk-based cocoa beverages; PRESSURE; BEHAVIOR; Food Science & Technology